The Difference in Pharmacokinetics and Pharmacodynamics between Extended-Release Fluvastatin and Immediate-Release Fluvastatin in Healthy Chinese Subjects - Xu, H. R. (Hindawi Publishing Corporation, 2012)
The aim of this study was to evaluate the difference in pharmacokinetics and pharmacodynamics between extended-release (ER) fluvastatin tablet and its immediate-release (IR) capsule in Chinese healthy subjects. This was an open-label, single/multiple-dose, two-period, two-treatment, crossover, randomized trial with a minimum washout period of 7 days. Twenty healthy male adult subjects were given fluvastatin ER tablet 80 mg QD by oral administration or fluvastatin IR capsule 40 mg BID for seven days. Blood samples were collected up to 24 hours after dosing on day 1 and day 7. Serum concentrations of fluvastatin were determined by LC-MS/MS. For fluvastatin ER tablet 80 mg QD, C(max) was 61.0 ± 39.0 and 63.9 ± 29.7 ng/mL, and AUC(0−24 h) was 242 ± 156 and 253 ± 91.1 ng·h/mL on day 1 and 7, respectively. For fluvastatin IR capsule 40 mg BID, C(max) was 283 ± 271 and 382 ± 255 ng/mL, and AUC(0−24 h) was 720 ± 776 and 917 ± 994 ng·h/mL on day 1 and day 7, respectively. The relative bioavailability of fluvastatin ER tablet 80 mg QD to fluvastatin IR capsule 40 mg BID is (45.3 ± 23.9)% and (43.3 ± 24.1)% on day 1 and day 7, respectively. T(max) for fluvastatin ER tablet was 2.50 and 2.60 h and for capsule was 0.78 and 0.88 h on day 1 and day 7, respectively. In the first period, compared to baseline, cholesterol decreased 15.3% in fluvastatin ER tablet 80 mg QD and 16.9% in fluvastatin IR capsule 40 mg BID. Triglyceride decreased 3.7% in fluvastatin ER tablet 80 mg QD and 19.1% in fluvastatin IR capsule 40 mg BID. The difference has no statistical significance at P > 0.05 in reduction percent of cholesterol and triglyceride between the two groups. No adverse events were recorded. The results indicated that C(max) of fluvastatin ER tablet is reduced and T(max) is prolonged compared with IR capsule. There is no accumulation for ER formulation after multiple doses.